Hubungan Komunikasi Terapeutik Dan Kualitas Pelayanan Perawat Dengan Kecemasan Pasien Pre Operasi Di RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Tedi Asep Sutrisno; Jebul Suroso (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: This study aimed to determine the correlation between therapeutic communication and nurse service quality with preoperative patient anxiety in RSUD dr. R. Goeteng Taroenadibrata Purbalingga. Method: The study was a quantitative descriptive study with cross-sectional method. The samples were preoperative patients who experienced anxiety in the surgical inpatient room with a total of 90 respondents. The samples were collected by using purposive sampling technique. There were three different types of questionnaires as the instruments of the study namely therapeutic communication questionnaire, nurse service quality questionnaire, and HARS questionnaire. Chi square statistical test was used to analyze the data. Results: The results of the analysis of the correlation between nurses therapeutic communication and preoperative patient anxiety obtained p-value of 0,000. It can be interpreted that p-value of a = 0.05. While the results of the analysis of the relationship between nurse service quality and preoperative patient anxiety obtained p-value of 0,000. It can be interpreted that p-value of a = 0.05. Conclusion: There is a correlation between nurse therapeutic communications and preoperative patient anxiety and there is a correlation between qualities of nurse services and preoperative patient anxiety in RSUD dr. R. Goeteng Taroenadibrata Purbalingga.